The Influence of Employee Engagement, Work Environment and Job Satisfaction on Organizational Commitment and Performance of Employees: A Sampling Weights in PLS path Modelling - Ahakwa, Isaac; Yang, Jingzhao; Agba Tackie, Evelyn; Atingabili, Samuel (SEISENSE (PRIVATE) LIMITED, 2021)
Purpose- This paper explored the link between employee engagement, work environment, and job satisfaction on organizational commitment and employee performance in Ghana's Banking sector considering moderated-mediated interaction. Design/Methodology- Data were obtained from seven hundred and twenty (720) employees from selected financial banks in the Greater Accra Region of Ghana through simple random probability sampling. However, seven hundred (700) responses were deemed accurate and therefore used in the analysis. In the analytical process, Weighted Partial Least Squares (WPLS) and Partial Least Squares (PLS) based on Structural Equation Modeling (SEM) were employed. Findings- From the findings, the studied data for both WPLS-SEM and PLS-SEM models met internal consistency reliability, convergent, and discriminant validity. Also, organizational commitment fully mediated the link between work environment and employee performance in the WPLS-SEM model compared to PLS-SEM with partial mediation. It was statistically significant at p<0.01. Practical Implications- Based on the findings, it’s recommended that organizations and managers focus on developing the workers' workplace environment in numerous ways. This should entail valuing workers' contributions, communicating the company's progress and achievement to workers, thus instilling ownership in workers, providing them with a work-life balance, providing the requisite knowledge and tools for successful production, and providing a stable atmosphere. The workplace of all these factors could increase workers' morale and lead to increased productivity.